O Teorema do tipo Dvoretzky-Rogers para sequências misto somáveis e resultados de espaçabilidade - Oliveira, Fabrícia Rodrigues de (2012)
In this work we study the spaces of absolutely, weakly and unconditionally p-summable sequences and the space of mixed (s; q)-summable sequences of a Banach space and we prove Dvoretzky-Rogers type Theorems for unconditionally (in particular weakly) p-summable sequences and for mixed (s; q)-summable sequences. Besides, we prove results about spaceability for several sequence sets, in special, for sets of mixed (s; q)-summable, weakly p-summable, unconditionally p-summable and absolutely p-summable sequences.